N-Butylphthalide Alleviates Blood–Brain Barrier Impairment in Rats Exposed to Carbon Monoxide - Bi, Mingjun; Zhang, Mingwei; Guo, Dadong; Bi, Weikang; Liu, Bin; Zou, Yong; Li, Qin (Frontiers in Pharmacology, 2016)
Carbon monoxide (CO) poisoning is one of the most important health concerns and may result in neuropathologic changes and neurologic sequelae. However, few studies have addressed the correlation between CO poisoning and blood-brain barrier (BBB) impairment. In this study, we investigated the effects of N-butylphthalide (NBP) on the expressions of zonula occludens-1 (ZO-1), claudin-5 and aquaporin-4 (AQP-4) proteins in a CO poisoning rat model. The results indicated that the brain water content was obviously increased, and the tight junctions (TJs) between endothelial cells were disrupted, resulting in significant cerebral edema and BBB dysfunction in a rat model of CO poisoning. Meanwhile, the ultrastructure of endothelial cells and pericytes was seriously damaged, and the expressions of ZO-1 and claudin-5 were decreased at an early stage (<7 days). NBP treatment could efficiently maintain the ultrastructural and functional integrity of BBB, alleviate cerebral edema. Besides, NBP could also markedly increase the levels of both ZO-1 and claudin-5 proteins compared with those in rats exposed to CO (P<0.05), whereas NBP had no apparent regulatory effect on AQP-4 expression. Taken together, this study highlights the importance of ZO-1 and claudin-5 proteins in maintaining BBB ultrastructure and function after CO poisoning. NBP, as a novel treatment approach, may effectively inhibit the down-regulation of ZO-1 and claudin-5 proteins (but not AQP-4), thereby preserving the barrier function and reducing cerebral edema after CO poisoning.